Chromosome level reference of Atlantic halibut Hippoglossushippoglossus provides insight into the evolution of sexual determination systems. (1st April 2021) - Einfeldt, Anthony L.; Kess, Tony; Messmer, Amber; Duffy, Steven; Wringe, Brendan F.; Fisher, Jonathan; den Heyer, Cornelia; Bradbury, Ian R.; Ruzzante, Daniel E; Bentzen, Paul
Abstract: Changes in the genetic mechanisms that control sexual determination have occurred independently across the tree of life, and with exceptional frequency in teleost fishes. To investigate the genomic changes underlying the evolution of sexual determination, we sequenced a chromosome‐level genome, multitissue transcriptomes, and reduced representation population data for the Atlantic halibut ( Hippoglossus hippoglossus ), which has an XY/XX sex determination mechanism and has recently diverged (0.9–3.8 Ma) from the Pacific halibut ( Hippoglossus stenolepis ), which has a ZZ/ZW system. We used frequency and coverage‐based population approaches to identify a putative sex‐determining factor, GSDF . We characterized regions with elevated heterozygosity and linkage disequilibrium indicating suppression of recombination across a nascent sex chromosome. We detected testis‐specific expression of GSDF, the sequence of which is highly conserved across flatfishes. Based on evidence from genome‐wide association, coverage, linkage disequilibrium, testis and brain transcriptomes, and sequence conservation with other flatfishes, we propose a mechanism for the recent evolution of an XY sex‐determination mechanism in Atlantic halibut. Changes to the ancestral sex‐determining gene DMRT1 in regulating the downstream gene GSDF probably coincided with GSDF, or a proximal regulatory element of it, becoming the primary sex‐determining factor. Our results suggest changes to a small number of elements can have drastic repercussions for the genomic substrate available to sex‐specific evolutionary forces, providing insight into how certain elements repeatedly evolve to control sex across taxa. Our chromosome‐level assembly, multitissue transcriptomes, and population genomic data provide a valuable resource and understanding of the evolution of sexual systems in fishes.